Juan Ramón Sepich: Argentine Catholic Hispanism as a Theory of Culture - Olalla, Marcos (Analysis. Journal of Philosophical Research, 2021)
In this work, the Hispanist phase (1930-1955) of the thought of Juan Ramón Sepich (1906-1979) —Argentinian priest and philosopher— is analyzed. The specificity of his way of integration to the Argentine nationalist thought as a cultural theorist is highlighted. The main topics of his philosophical discourse in this stage, the elements of such discourse that operated in his work as a publicist of the Francoism, and the ups and downs of his links with early Peronism are described.